PENINGKATAN EFEKTIFITAS METODE KANGURU TERHADAP KECUKUPAN ASI PADA BAYI CUKUP BULAN DI DESA SUKARAME BARU KEC. KUALUH HULU KAB. LABUHAN BATU UTARA - Isyos Sari Sembiring; Sisca Suci Triana Ginting; Nur Azizah; Basaria Manurung; Fera Susanti; Devita Purnama Sari; Cindi Hidayat (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2021)
Infants aged 0-28 days is a critical period for the baby's life, 2/3 of infant deaths occur within 4 weeks after delivery and 60% of newborn deaths occur within 7 days after birth. Good monitoring and care for both mother and baby during the puerperium can prevent some of these deaths. If the experience of breastfeeding mothers is well managed, then mothers can breastfeed more successfully, if they have more contact with their babies. Breastfeeding stimulates the production of prolactin so that it will increase the volume and stimulate the milk ejection reflex. The closest contact occurs when the mother uses the kangaroo (skin to skin) method. As we know, kangaroos put their young in a pouch that is in direct contact with the mother's body, after research it turned out that this method was able to suppress infant mortality. Kangaroo care tries to provide closeness between the mother and the newborn. Put the baby in direct skin-to-skin contact. This ensures physiological and psychological warmth and bonding between mother and baby. This kangaroo technique was first introduced by Neosedgar Rey and Hector Martine in Bogota in 1978. Subsequent research conducted by Larimer on the kangaroo technique showed advantages for infants and parents, babies do not experience apnea and bradycardia, regulate body temperature, increase body weight and are effective for breast-feed. This general problem is also faced in Sukarame Baru Village, Kec. Kualuh Hulu Kab. Labuhan Batu Utara Medan who interviewed 2 employees of RB Khadijah said that they had never done the kangaroo method because they were lazy and did not know the procedure for doing the kangaroo method, the mother's enthusiasm for increasing breast milk adequacy was quite high but the scheduled program was not optimal. The purpose of this service program (PKM) is to improve the quality of breast milk adequacy for breastfeeding mothers by using the kangaroo method. The results of the community service program activities that have been carried out show that the results of the study show that the effectiveness of the kangaroo method on the adequacy of breast milk in term infants and an independent t-test was performed. It was found that the average frequency of urination in the intervention group after the kangaroo method was 5 times. per day with a standard deviation of 1.36 while in the control group the average BAK frequency was 4 times per day with an SD of 1.41. The results of the statistical test showed that the P value was 0.023, so it can be concluded that there is a significant difference in the average frequency of urination by the kangaroo method in the intervention group and the control group. The average frequency of defecation after being carried out in the intervention group after the kangaroo method was 4 times per day with an SD of 1.49, while in the control group the average frequency of defecation was 3 times per day with an SD of 1.57. The results of the statistical test showed that the P value was 0.040, so it can be concluded that there is a significant difference in the average frequency of defecation after the kangaroo method was used in the intervention group and the control group. Infants aged 0-28 days is a critical period for the baby's life, 2/3 of infant deaths occur within 4 weeks after delivery and 60% of newborn deaths occur within 7 days after birth. Good monitoring and care for both mother and baby during the puerperium can prevent some of these deaths. If the experience of breastfeeding mothers is well managed, then mothers can breastfeed more successfully, if they have more contact with their babies. Breastfeeding stimulates the production of prolactin so that it will increase the volume and stimulate the milk ejection reflex. The closest contact occurs when the mother uses the kangaroo (skin to skin) method. As we know, kangaroos put their young in a pouch that is in direct contact with the mother's body, after research it turned out that this method was able to suppress infant mortality. Kangaroo care tries to provide closeness between the mother and the newborn. Put the baby in direct skin-to-skin contact. This ensures physiological and psychological warmth and bonding between mother and baby. This kangaroo technique was first introduced by Neosedgar Rey and Hector Martine in Bogota in 1978. Subsequent research conducted by Larimer on the kangaroo technique showed advantages for infants and parents, babies do not experience apnea and bradycardia, regulate body temperature, increase body weight and are effective for breast-feed. This general problem is also faced in Sukarame Baru Village, Kec. Kualuh Hulu Kab. Labuhan Batu Utara Medan who interviewed 2 employees of RB Khadijah said that they had never done the kangaroo method because they were lazy and did not know the procedure for doing the kangaroo method, the mother's enthusiasm for increasing breast milk adequacy was quite high but the scheduled program was not optimal. The purpose of this service program (PKM) is to improve the quality of breast milk adequacy for breastfeeding mothers by using the kangaroo method. The results of the community service program activities that have been carried out show that the results of the study show that the effectiveness of the kangaroo method on the adequacy of breast milk in term infants and an independent t-test was performed. It was found that the average frequency of urination in the intervention group after the kangaroo method was 5 times. per day with a standard deviation of 1.36 while in the control group the average BAK frequency was 4 times per day with an SD of 1.41. The results of the statistical test showed that the P value was 0.023, so it can be concluded that there is a significant difference in the average frequency of urination by the kangaroo method in the intervention group and the control group. The average frequency of defecation after being carried out in the intervention group after the kangaroo method was 4 times per day with an SD of 1.49, while in the control group the average frequency of defecation was 3 times per day with an SD of 1.57. The results of the statistical test showed that the P value was 0.040, so it can be concluded that there is a significant difference in the average frequency of defecation after the kangaroo method was used in the intervention group and the control group.